2012
DOI: 10.1007/s15010-012-0360-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of 16 periprosthetic shoulder joint infections

Abstract: As recommended for hip and knee PJI, we suggest treating shoulder PJI with a low-grade infection by microorganisms such as P. acnes with an exchange of the prosthesis. Cohort studies are needed to verify our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…The implementation of algorithms seems beneficial to establish clinical recommendations that can be followed even by the non-expert. Even though established for hip and knee joint prostheses, and suggested for other PJI [29,30], very few data is available on the actual implementation in clinical routine [4,5,7,12]. We are therefore presenting the results of our PJI algorithm in clinical day-to-day routine on a collective of 147 cases without selection bias or exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of algorithms seems beneficial to establish clinical recommendations that can be followed even by the non-expert. Even though established for hip and knee joint prostheses, and suggested for other PJI [29,30], very few data is available on the actual implementation in clinical routine [4,5,7,12]. We are therefore presenting the results of our PJI algorithm in clinical day-to-day routine on a collective of 147 cases without selection bias or exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…13-17 Shoulder ODRIs, however, may have higher Propionibacterium (P.) acnes prevalence, at up to 38%. 19 Recently, more attention has been focussed upon polymicrobial infections, which may account for 10%-20% of cases. 13,14,17 Furthermore, studies using molecular diagnostic techniques indicate that, in addition, there is a significant proportion (5%-34%) of culture-negative infections.…”
Section: The Clinical and Microbiological Challenges Of Modern Devicementioning
confidence: 99%
“…Penicillin and ceftriaxone are recommended first line therapies [1]. One study suggested that one-stage exchange of the prosthesis may be possible [53]. In an animal model study, the combination of daptomycin and rifampin was associated with a cure rate of 63% [72], which was higher than other agents used in conjunction with rifampin, including vancomycin, penicillin G, ceftriaxone, levofloxacin and clindamycin.…”
Section: Treatmentmentioning
confidence: 99%